Multi-Stakeholder Partnerships (MSPs) for accelerating varietal turnover for sorghum, groundnut and common bean in Tanzania: The case of Mbamba MTE Company Ltd - Radegunda, Kessy; Ochieng, Justus; Mwakatwila, Atupokile; Edith Kadege; Papias Binagwa; Mwenda, Emmanuel; Joachim Madeni; Reinfrid Maganga; Chima Rickards; Victor Lesedy; Rubyogo, Jean Claude; Eliud Kongola (2025)
Mbamba MTE Company Limited, established in 2019 in Dodoma, Tanzania, works with over 81,000 smallholder farmers across Dodoma, Manyara, and Singida regions, primarily in grain trading and seed multiplication. Despite its strong farmer network, the company faces persistent challenges in sourcing adequate volumes of clean, high-quality grain—largely due to farmers’ reliance on poor-quality seed and use of rudimentary post-harvest technologies. These limitations result in mixed, broken, and poorly cleaned grains, while also placing a heavy labor burden on women and youth through manual threshing and shelling.